Effects of high-intensity interval and moderate-intensity continuous training on ambulatory blood pressure and cardiovascular outcomes in older adults with hypertension (HEXA Study): study protocol for a randomised trial - Francisco Dalton-Alves; Maria Beatriz F Araújo; Bruno Erick B Lucena; Gabriel C Souto; Daniele Samara D Lopes; Maria Isabel S Lucena; Raíssa de Melo Silva; Ludmila L P Cabral; Yuri A Freire; Fabíola L Golveia; Telma Maria Araújo Lemos; Rodrigo A V Browne; et al. (BMJ Open)
Introduction Approximately two-thirds of Brazilian older adults have hypertension. Aerobic training is the first-line non-pharmacological therapy for hypertension. However, the effects of different aerobic training approaches on ambulatory blood pressure in older adults are uncertain. Here, we present the study protocol for the HEXA Study, which aims to investigate the effects of high-intensity interval (HIIT) and moderate-intensity continuous training (MICT) on 24-hour ambulatory blood pressure and cardiovascular outcomes in older adults with hypertension.Methods and analysis This is a single-centre, randomised, three-arm, parallel superiority trial with a 1:1:1 ratio. The trial is conducted with blinded outcome assessors and statistical analysts. 66 inactive older adults with hypertension aged 60–80 years without a history of major adverse cardiovascular events will be randomly assigned to one of the following groups: (1) HIIT (3 months; 3× week); (2) MICT (3 months; 3× week); (3) health education programme (control; 3 months; 1× week). Exercise training sessions involve rating of perceived exertion-based outdoor moderate walking, brisk walking and/or jogging. The primary outcome is 24-hour ambulatory blood pressure. Secondary cardiovascular outcomes are resting blood pressure, cardiorespiratory fitness, pulse wave velocity, carotid intima-media thickness, heart rate variability and cardiac function/structure. All outcomes are measured at baseline and after a 3-month period. In addition, feelings of pleasure/displeasure, adherence and safety are reported.Ethics and dissemination All procedures were approved by the Research Ethics Committee of the Onofre Lopes University Hospital (protocol, CAAE 07191019.8.0000.5292) and are executed in compliance with the Declaration of Helsinki. Additionally, the procedures adhered to Resolution 466/2012 issued by the Brazilian National Health Council for research involving human subjects.Trial registration number Brazilian Registry of Clinical Trials (ID: RBR-4ntszb).